Why do thioureas and squaramides slow down the Ireland–Claisen rearrangement? - Krištofíková, Dominika; Filo, Juraj; Mečiarová, Mária; Šebesta, Radovan (Beilstein Journal of Organic Chemistry, 2019)
A range of chiral hydrogen-bond-donating organocatalysts was tested in the Ireland–Claisen rearrangement of silyl ketene acetals. None of these organocatalysts was able to impart any enantioselectivity on the rearrangements. Furthermore, these organocatalysts slowed down the Ireland–Claisen rearrangement in comparison to an uncatalyzed reaction. The catalyst-free reaction proceeded well in green solvents or without any solvent. DFT calculations showed that the activation barriers are higher for reactions involving hydrogen-donating organocatalysts and kinetic experiments suggest that the catalysts bind stronger to the starting silyl ketene acetals than to transition structures thus leading to inefficient rearrangement reactions.
Keywords: DFT calculations; green solvents; H-bonding catalysts; Ireland–Claisen rearrangement; silyl ketene acetals

(untitled) - Ireland, R. E.; Mueller, R. H. (J. Am. Chem. Soc., 1972)

(untitled) - Ireland, R. E.; Willard, A. K. (Tetrahedron Lett., 1975)

(untitled) - Ireland, R. E.; Wilcox, C. S. (Tetrahedron Lett., 1977)

(untitled) - Davies, S. G.; Fletcher, A. M.; Roberts, P. M.; Thomson, J. E.; Zammit, C. M. (Chem. Commun., 2013)

(untitled) - Krebs, A.; Kazmaier, U. (Tetrahedron Lett., 1996)

(untitled) - Srikrishna, A.; Khan, I. A.; Babu, R. R.; Sajjanshetty, A. (Tetrahedron, 2007)

(untitled) - Churcher, I.; Williams, S.; Kerrad, S.; Harrison, T.; Castro, J. L.; Shearman, M. S.; Lewis, H. D.; Clarke, E. E.; Wrigley, J. D. J.; Beher, D.; Tang, Y. S.; Liu, W. (J. Med. Chem., 2003)

(untitled) - Kraft, P.; Denizot, N. (Eur. J. Org. Chem., 2013)

(untitled) - Liu, D.; Yu, X.; Huang, L. (Chin. J. Chem., 2013)

(untitled) - Dittrich, N.; Jung, E.-K.; Davidson, S. J.; Barker, D. (Tetrahedron, 2016)

(untitled) - Tellam, J. P.; Carbery, D. R. (J. Org. Chem., 2010)

(untitled) - Ito, H.; Taguchi, T. (Chem. Soc. Rev., 1999)

(untitled) - Chai, Y.; Hong, S.-p.; Lindsay, H. A.; McFarland, C.; McIntosh, M. C. (Tetrahedron, 2002)

(untitled) - Welch, J. T.; Samartino, J. S. (J. Org. Chem., 1985)

(untitled) - Godenschwager, P. F.; Collum, D. B. (J. Am. Chem. Soc., 2008)

(untitled) - Welch, J. T.; Plummer, J. S.; Chou, T. S. (J. Org. Chem., 1991)

(untitled) - Liu, D.; Yu, X. (Tetrahedron Lett., 2012)

(untitled) - Kobayashi, M.; Masumoto, K.; Nakai, E.-i.; Nakai, T. (Tetrahedron Lett., 1996)

(untitled) - Araki, K.; Welch, J. T. (Tetrahedron Lett., 1993)

(untitled) - Uchiyama, H.; Kawano, M.; Katsuki, T.; Yamaguchi, M. (Chem. Lett., 1987)

(untitled) - Koch, G.; Janser, P.; Kottirsch, G.; Romero-Giron, E. (Tetrahedron Lett., 2002)

(untitled) - Corey, E. J.; Lee, D. H. (J. Am. Chem. Soc., 1991)

(untitled) - Seizert, C. A.; Ferreira, E. M. (Chem. – Eur. J., 2014)

(untitled) - Kazmaier, U. (Liebigs Ann./Recl., 1997)

(untitled) - Burke, S. D.; Fobare, W. F.; Pacofsky, G. J. (J. Org. Chem., 1983)

(untitled) - Kazmaier, U.; Krebs, A. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Wong, K. C.; Ng, E.; Wong, W.-T.; Chiu, P. (Chem. – Eur. J., 2016)

(untitled) - Moyano, A.; El-Hamdouni, N.; Atlamsani, A. (Chem. – Eur. J., 2010)

(untitled) - Tantillo, D. J. (Acc. Chem. Res., 2016)

(untitled) - Li, G.-Q.; Gao, H.; Keene, C.; Devonas, M.; Ess, D. H.; Kürti, L. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, J.-Z.; Zhou, J.; Xu, C.; Sun, H.; Kürti, L.; Xu, Q.-L. (J. Am. Chem. Soc., 2016)

(untitled) - Gao, H.; Xu, Q.-L.; Keene, C.; Yousufuddin, M.; Ess, D. H.; Kürti, L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Rueping, M.; Antonchick, A. P. (Angew. Chem., Int. Ed., 2008)

(untitled) - Maity, P.; Pemberton, R. P.; Tantillo, D. J.; Tambar, U. K. (J. Am. Chem. Soc., 2013)

(untitled) - Uyeda, C.; Jacobsen, E. N. (J. Am. Chem. Soc., 2008)

(untitled) - Uyeda, C.; Rötheli, A. R.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2010)

(untitled) - Uyeda, C.; Jacobsen, E. N. (J. Am. Chem. Soc., 2011)

(untitled) - Kirsten, M.; Rehbein, J.; Hiersemann, M.; Strassner, T. (J. Org. Chem., 2007)

(untitled) - Ganem, B. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Shanab, K.; Neudorfer, C.; Spreitzer, H. (Curr. Org. Chem., 2016)

(untitled) - Tang, S.; Zhao, H. (RSC Adv., 2014)

(untitled) - Chai, J.-D.; Head-Gordon, M. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Mardirossian, N.; Head-Gordon, M. (Mol. Phys., 2017)